Operaciones: Conjunción de matrices booleanas - Chavarría-Molina, Jeffry (My University, 2018)
En el presente vídeo se define la operación conjunción de matrices booleanas, y la interpretación de sus resultados en términos de relaciones. Este vídeo finaliza explicando detalladamente las condiciones necesarias, así como el procedimiento para realizar la operación indicada.

In this video, the operation of Boolean matrices is defined, and the interpretation of its results in terms of relationships. This video ends by explaining in detail the necessary conditions, as well as the procedure to perform the indicated operation.
Keywords: Operaciones matemáticas; Matrices; Matemáticas discretas; Mathematical operations; Arrays; Discrete mathematics